The genome sequence of the European peacock butterfly, Aglais io (Linnaeus, 1758) [version 1; peer review: 3 approved] - Roger Vila; Alexander Mackintosh; Konrad Lohse (Wellcome Open Research, 2021)
We present a genome assembly from an individual male Aglais io (also known as Inachis io and Nymphalis io) (the European peacock; Arthropoda; Insecta; Lepidoptera; Nymphalidae). The genome sequence is 384 megabases in span. The majority (99.91%) of the assembly is scaffolded into 31 chromosomal pseudomolecules, with the Z sex chromosome assembled. Gene annotation of this assembly on Ensembl has identified 11,420 protein coding genes.